Glucocorticosteroids do not impact directly growth rate and biomass of Rhizopus arrhizus (syn. R. oryzae) in vitro - Bellanger, AP (Virulence, 2015)
Glucocorticoid (GC) use is a common risk factor for invasive fungal infections. This is attributed to the complex dysregulation of immunity caused by GCs. However, studies have demonstrated increased growth with GC exposure for some molds, such as Aspergillus fumigatus and Exserohilum rostratum. No such data exist for Mucorales. Therefore, we investigated the influence of GC exposure on the growth of Rhizopus arrhizus (syn. R. oryzae) in different culture media and in different atmospheres. We measured continuous spore growth using spectrophotometry and biomass variations using XTT assay. We did not observe enhanced growth or biomass variation with any of the GCs regardless of the medium or conditions. These results support the existence of fungus-specific differences in the effect of GCs on fungal biology.